2020
DOI: 10.3390/ijerph17072177
|View full text |Cite
|
Sign up to set email alerts
|

Does Playing Video Games Increase Emotional Creativity?

Abstract: Emotional creativity (EC), which constitutes a main aspect of the general creativity concept, is often shown to be substantially related to positive emotional experiences, effective motivation, and innovation at the workplace as well as at school. However, little is known about the relationship between emotional creativity and the time people tend to spend playing video games. Nowadays, video games and virtual reality have become an important aspect of public health and psychological research. They constitute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Studies on the relationship between board games and creativity are not new (Butler, 1988), and more recent work has focused on the creative potential of individuals (Mercier & Lubart, 2021), the relationship between games, empathy and creativity (Rosa et al, 2021), and the development of problemsolving skills (Chen et al, 2021). Many studies have investigated the effects of video games on creativity (Čábelková et al, 2020;Gackenbach & Dopko, 2012;Green & Kaufman, 2015;Hamlen, 2009;Shute & Rahimi, 2021;Yeh, 2015), and video games are also known to be effective ways to support the development of certain perceptual, attentional and cognitive skills (Bediou et al, 2018), along with certain social and emotional skills (Kovess-Masfety et al, 2016;Villani et al, 2018).…”
Section: Limits Of Our Study and Implications Regarding Fostering Psy...mentioning
confidence: 99%
“…Studies on the relationship between board games and creativity are not new (Butler, 1988), and more recent work has focused on the creative potential of individuals (Mercier & Lubart, 2021), the relationship between games, empathy and creativity (Rosa et al, 2021), and the development of problemsolving skills (Chen et al, 2021). Many studies have investigated the effects of video games on creativity (Čábelková et al, 2020;Gackenbach & Dopko, 2012;Green & Kaufman, 2015;Hamlen, 2009;Shute & Rahimi, 2021;Yeh, 2015), and video games are also known to be effective ways to support the development of certain perceptual, attentional and cognitive skills (Bediou et al, 2018), along with certain social and emotional skills (Kovess-Masfety et al, 2016;Villani et al, 2018).…”
Section: Limits Of Our Study and Implications Regarding Fostering Psy...mentioning
confidence: 99%
“…Recently, Peschl and Fundneider [11] developed the entire innovation paradigm as a systematic innovation process approach, which is now called "emerging innovation". Comparing this process with traditional approaches to innovation and knowledge creation, it becomes clear that it goes beyond traditional out-of-the-box thinking and creative tools [12]. These changes require a dynamic representation of innovation as a knowledge process.…”
Section: Enabling Spaces For Collaborative Knowledge Creation Innovationmentioning
confidence: 99%
“…The younger population is especially drawn to gaming due to their innate need for play and the easy accessibility of digital devices (Khazaie & Derakhshan, 2021). Recent studies (e.g., Čábelková et al, 2020;Donati et al, 2021;Du et al, 2021;Leonhardt & Overå, 2021;Jang et al, 2021) have examined the impact of gaming on various aspects of second language foreign language acquisition, including cognitive abilities, psychological well-being, creativity, social interaction, isolation, and communicative competence. Additionally, prior research has demonstrated the effectiveness of virtual reality in enhancing foreign language acquisition (Pinto et al, 2021).…”
Section: Introductionmentioning
confidence: 99%